Erica Tietze-Conrat, Tagebücher (1937-1938) Band II: Mit den Mitteln der Disziplin - Caruso, Alexandra (2015)
In 1937 and 1938 her journals give an interesting view of the networks between museumstafs, art dealers, art scholars and artists just before the outbreak of World War II.